A study of R&D portfolio management among UK organisations. (9th October 2006) - Szwejczewski, Marek; Mitchell, Rick; Lemke, Fred
Portfolio management is a decision process where a company's list of active new products is constantly updated and revised. In this process, new products are evaluated, selected and prioritised, with resources being allocated accordingly. Portfolio management is considered to be an important activity, but research suggests that it may be one of the weakest areas in a company's new product development process. While many methods have been proposed, there have been very few studies of their actual usage, especially by UK-based companies. This paper presents research into how seven UK manufacturing companies (from several industrial sectors) managed their portfolios of Research and Development (R&D) projects.